Development of E-module on Static Fluid Material Containing Local Wisdom of the East Coast of North Sumatra Using Flip Pdf Professional - Siregar, Rodearna; Harahap, Mukti Hamjah; Irfandi, Irfandi (Universitas Negeri Padang, 2024)
Physics learning is trapped in a routine where learning activities only provide formulas, example questions and exercises, the teaching materials used by teachers are less contextual, still in the form of school textbooks, causing students' ignorance about the use of physics in everyday life so that the knowledge they have students tend to memorize. This research aims to develop a physics e-module based on local wisdom with the help of a professional PDF flip that is valid, practical and effective for use as teaching material, contextual in nature to increase students' understanding of concepts. This type of research is research and development (Research and Development) with the ADDIE development model including the stages of analysis, design, development, implementation and evaluation. The instruments of this research are validation sheets, questionnaires and learning tests. Data was analyzed using Excel. The research results show that the e-module developed is valid with a material expert validation percentage of 90.62%, media expert validation of 87%. The results of the practicality test by the teacher obtained a percentage of 96%, and the percentage of small group student questionnaire responses was 86.43%, the large group was 82.95% in the very practical category. The results of the effectiveness test based on the pretest-posttest learning outcomes obtained an average N-gain in the small group, namely 0.87 and in the large group, namely 0.92 in the high category, so that the physics e-module based on local wisdom is effectively used as physics teaching material because able to improve understanding of concepts.